Designing for fake news literacy training: A problem-based undergraduate online-course. (August 2021) - Scheibenzuber, Christian; Hofer, Sarah; Nistor, Nicolae
Abstract: In the wake of the Covid-19 pandemic, most universities had to switch to "emergency online learning". At the same time, academics were in search of means to combat "the infodemic", a wave of misinformation rolling over the world, affecting social and political life, and undermining efforts to deal with the pandemic. In the framework of emergency online learning, we propose an educational sciences undergraduate online course addressing fake news illiteracy by giving students an insight into the form and effects of fake news with a focus on framing. The course was built upon current fake news research and the problem-based learning approach. The research questions addressed students' perceptions of critical design elements, their fake news credibility test performance, and their academic achievement. A total of N = 102 undergraduate students participated in the course. Among various design elements, students indicated that online communication and feedback was most appealing. On the other hand, for future course iterations, they suggested improvements to the task descriptions. Fake news credibility decreased significantly ( F (1, 36) = 62.64, p < 0.000, partial η 2 = 0.64) and final course papers were on average good to very good, indicating strong academic achievement. The study suggests that problem-based online courses can be appropriate learning environments, even in the context of "emergency online learning" and, furthermore, that they can serve as an instrument for combating fake news illiteracy. Highlights: We address emergency online learning and infodemic during Covid-19 pandemic. We review current literature on online news cognitive processing and problem-based instructional design. We design, develop and test an educational sciences undergraduate online problem-based course on fake news. Student feedback on the appeal of certain design elements was mostly positive; improvements of others were suggested. Student fake news credibility assessment strongly improved; course papers reflected good to very good academic achievement.